Multitargeted combination effects of a triherbal formulation containing ELP against osteoporosis: in vitro evidence. (28th March 2016) - Ko, Chun Hay; Lau, Kit Man; Chau, Lily; Cheung, David Wing Shing; Siu, Wing Sum; Wong, Hing Lok; Shum, Wai Ting; Gao, Si; Fung, Kwok Pui; Leung, Ping Chung; Poon, Simon Kar‐Sing; Lau, Clara Bik San
Abstract: Objectives: An anti‐osteoporotic herbal formula ELP containing Epimedii Herba (E), Ligustri Lucidi Fructus (L) and Psoraleae Fructus (P) was studied to investigate the herb–herb interaction (or the possible synergistic effect) among each component and to identify the principal herbs in different modes of action. Methods: Rat osteoblast‐like UMR‐106 cells proliferation, rat MSCs‐derived osteoblastogenesis and RANKL‐induced RAW 264.7 osteoclastogenesis were adopted to investigate the bone‐forming activity and bone‐degrading activity of the herbal extracts. In the statistical aspect, a modified Tallarida's approach was employed to assess the synergistic effects in herbal combinations. Key findings: Psoraleae Fructus is the active herb for stimulating osteoblast proliferation, and mild synergy was detected in the pairwise combinations EL, LP and formula ELP. In osteoblastogenesis assay, E and L are the principal herbs for promoting osteoblast differentiation and significant synergy was detected in the pairwise combination EL. For inhibiting osteoclast formation, L is the active herb and significant synergy was detected in the 3‐way combination ELP. Conclusions: The presence of E, L and P is essential for ELP formula as a whole to act against osteoporosis via enhancing bone formation and reducing bone reabsorption. An optimal dosage at 150 μg/ml was proposed for ELP based on our findings.